2016
DOI: 10.1080/10790268.2016.1184828
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and access to healthcare services among community-dwelling people living with spinal cord injury

Abstract: The delivery of care for people with SCI with low socioeconomic status may be remodeled to include patient-centered medical homes where care is directed by an SCI physiatrist. Further increased telehealth efforts would allow for SCI physiatrists to monitor health conditions remotely and focus on preventative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 25 publications
1
57
0
1
Order By: Relevance
“…The literature reports GP visit rates between 77 and 86%. 14,[39][40][41] In-patient hospitalization rates following initial rehabilitation were reported to range between 19 and 57% 6 and were reported as low as 13% 1 in the succeeding years. The present study found a slightly higher GP visit rate (88%), whereas the in-patient hospitalization rate (36%) was within the range described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports GP visit rates between 77 and 86%. 14,[39][40][41] In-patient hospitalization rates following initial rehabilitation were reported to range between 19 and 57% 6 and were reported as low as 13% 1 in the succeeding years. The present study found a slightly higher GP visit rate (88%), whereas the in-patient hospitalization rate (36%) was within the range described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Moreover, persons with SCI often require a comprehensive array of general, specialized and home-based health care services. 4 In these services, providers from different specialties are engaged including medical doctors and therapists, 5 and complementary and alternative medical services are claimed, based on patient preference. 6 Besides unplanned visits, as a result of secondary acute complications of SCI, planned visits are commonly offered to persons with SCI as annual check-ups.…”
Section: Introductionmentioning
confidence: 99%
“…Telehealth, when conducted by an experienced physiatrist, can efficiently link underserved areas with SCI specialists while minimizing extraneous expenses. 19 Unfortunately, motivating this population to participate in telehealth can prove challenging. Multiple studies have shown that lower participation rates in programs to improve health in the SCI population are correlated with lower incomes.…”
Section: Discussionmentioning
confidence: 99%
“…36 Additionally, a cohort study found that visits to a physiatrist were significantly lower in patients living in a rural area (p = 0.008). 19 One study reported a 14% decrease in participation rates for every twofold increase in travel distance. 5 Finally, the perception of physical barriers (e.g., accessibility) and actual lack of services were significantly higher in the rural group (p = 0.002 and p = 0.042, respectively).…”
Section: Ruralitymentioning
confidence: 99%